2017
DOI: 10.1002/cphc.201700297
|View full text |Cite
|
Sign up to set email alerts
|

AgI/TMG‐Promoted Cascade Reaction of Propargyl Alcohols, Carbon Dioxide, and 2‐Aminoethanols to 2‐Oxazolidinones

Abstract: Chemical valorization of CO2 to access various value‐added compounds has been a long‐term and challenging objective from the viewpoint of sustainable chemistry. Herein, a one‐pot three‐component reaction of terminal propargyl alcohols, CO2, and 2‐aminoethanols was developed for the synthesis of 2‐oxazolidinones and an equal amount of α‐hydroxyl ketones promoted by Ag2O/TMG (1,1,3,3‐tetramethylguanidine) with a TON (turnover number) of up to 1260. By addition of terminal propargyl alcohol, the thermodynamic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…In all the papers, yields of oxazolidinones and ketones by-product are comparable. Authors performed control experiments, DFT calculation, kinetic and NMR studies and from these data suggested the reaction pathway depicted in Scheme 22 [177], which was confirmed in the other papers. The first proposed catalyst was the couple Ag 2 O and tetramethylguanidine (Scheme 22) [177].…”
Section: Scheme 13supporting
confidence: 66%
See 2 more Smart Citations
“…In all the papers, yields of oxazolidinones and ketones by-product are comparable. Authors performed control experiments, DFT calculation, kinetic and NMR studies and from these data suggested the reaction pathway depicted in Scheme 22 [177], which was confirmed in the other papers. The first proposed catalyst was the couple Ag 2 O and tetramethylguanidine (Scheme 22) [177].…”
Section: Scheme 13supporting
confidence: 66%
“…Authors performed control experiments, DFT calculation, kinetic and NMR studies and from these data suggested the reaction pathway depicted in Scheme 22 [177], which was confirmed in the other papers. The first proposed catalyst was the couple Ag 2 O and tetramethylguanidine (Scheme 22) [177]. The reaction was also applied to diols; 1-phenylethan-1,2-diol and 3-phenoxypropan-1,2-diol gave the corresponding cyclic carbonates in 95% and 58%, respectively.…”
Section: Scheme 13supporting
confidence: 66%
See 1 more Smart Citation
“…165,166 The Ag 2 O/1,1,3,3-tetramethylguanidine (TMG) catalytic system was also demonstrated to be an effective catalytic method by He's group in a three-component reaction of terminal propargylic alcohols, CO 2 , and 1,2-diols for the formation of cyclic carbonates and α-hydroxyl ketones. 168 The addition of terminal propargyl alcohols overcame the thermodynamic limitations in the condensation reaction of 1,2-diols with CO 2 .…”
Section: Thermodynamic Favorable Processesmentioning
confidence: 99%
“…To shift the equilibrium to 2-oxazolidinones, harsh reaction conditions [43][44][45][46][47], dehydrating agents or auxiliaries are often needed [13,[48][49][50][51]; thus the generation of wasteful by-products is unavoidable. As an alternative strategy, our group introduced propargyl alcohols into the reaction system of amino alcohols and CO2 to circumvent this thermodynamic limitation [52][53][54]. As descripted in Scheme 1, this three-component cascade reaction is composed of carboxylative cyclization and the following intermolecular nucleophilic ring-opening and further intramolecular nucleophilic cyclization.…”
Section: Introductionmentioning
confidence: 99%